Risk Factors for Prolonged Length of Stay of Older Patients in an Academic Emergency Department: A Retrospective Cohort Study - Özcan Sir; Gijs Hesselink; Mara Van Den Bogaert; Reinier P. Akkermans; Yvonne Schoon (Emergency Medicine International)
Emergency departments (EDs) are challenged with a growing population of older patients. These patients are at risk for a prolonged length of stay (LOS) at the ED and face more complications and poorer clinical outcomes. We aimed to identify risk factors for a prolonged LOS of older patients at the ED. For this retrospective clinical database study, we analyzed medical records of 2000 patients ≥70 years old presenting at the ED of a large level I trauma center in the Netherlands. LOS above the 75th percentile of LOS at our ED, 293 minutes, was considered prolonged. After bivariate analysis, we identified associations between LOS and patient, organizational, and clinical factors. Associations with a p < 0.05 were inserted in multivariable logistic regression models. We analyzed 1048 men (52%) and 952 women (48%) with a mean age of 78 ± 6.2 years. Risk factors for prolonged LOS of older patients at the ED were follows: higher number (more than one) of consultations (OR [odds ratio] 2.4, CI [confidence interval] 2.0-2.91), or diagnostic interventions (OR 1.5, CI 1.4-1.7); presenting complaints of a neurological (OR 2.2, CI 1.0-4.5) or internal medicine focus (OR 2.6, CI 1.4-4.6); patients with an altered consciousness (OR 3.3, CI 1.6-6.6); treatment by physicians of the departments of surgery (OR 3.4, CI 2.2-5.2), internal medicine (OR 2.6, CI 1.9-3.7), or pulmonology (OR 2.2, CI 1.4-3.6); and urgency category of ≥ U1. Awareness of factors associated with prolonged LOS of older patients presenting at the ED is essential. Physicians should recognize and take these factors into account, in order to improve clinical outcomes of the (strongly increasing) population of older patients at the ED.